Time-dependent reliability assessment of a simply supported girder bridge based on the third-moment method. (April 2023) - Wang, Jiao; Wu, Zengcong; Ye, Xinying
Abstract: Concrete bridges decay over time due to environmental or operational processes, leading to a reduction in their reliability. In this paper, a new time-dependent reliability evaluation procedure is proposed taking into consideration the simultaneous non-stationarities of vehicle load effect and resistance deterioration. Using the third-moment (3M) method and the second-moment (2M) method, the time-varying reliability of a simply supported girder bridge was investigated. The 3M method is a novel approach to calculate the reliability index requiring neither iteration nor computation of derivatives. As validated by Monte-Carlo simulations, it is shown that the 3M method is more accurate than the 2M method. Based on different moment methods, the effects of parameters such as the growth rate of vehicle load and the time proportions of different operation states in the reliability of the system were investigated. By analyzing the relationship between the time-dependent reliability index and the target reliability index, the time points of maintenance and inspection were predicted.